1997
DOI: 10.1038/36599
|View full text |Cite
|
Sign up to set email alerts
|

DAP kinase links the control of apoptosis to metastasis

Abstract: DAP kinase is a new type of calcium/calmodulin-dependent enzyme that phosphorylates serine/threonine residues on proteins. Its structure contains ankyrin repeats and the 'death' domain, and it is associated with the cell cytoskeleton. The gene encoding DAP kinase was initially isolated as a positive mediator of apoptosis induced by interferon-gamma, by using a strategy of functional cloning. We have now tested whether this gene has tumour-suppressive activity. We found that lung carcinoma clones, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
301
3
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(316 citation statements)
references
References 29 publications
8
301
3
3
Order By: Relevance
“…DAP kinase signi®cantly induced apoptosis upon overexpression and IFN-g-induced apoptosis was inhibited by transfection of the kinase negative mutant of DAP kinase . Furthermore, cells transfected with DAP kinase were more sensitive to apoptosis induced by TNF-a and the cells costimulated with TNF-a and cycloheximide resulted in faster migration of the DAP kinase protein on SDS ± PAGE, probably due to protein modi®cations such as protein phosphorylation or cleavage by proteases (Inbal et al, 1997). These results suggest that DAP kinase may be a key signaling molecule in not only IFN-g but also TNF-a-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…DAP kinase signi®cantly induced apoptosis upon overexpression and IFN-g-induced apoptosis was inhibited by transfection of the kinase negative mutant of DAP kinase . Furthermore, cells transfected with DAP kinase were more sensitive to apoptosis induced by TNF-a and the cells costimulated with TNF-a and cycloheximide resulted in faster migration of the DAP kinase protein on SDS ± PAGE, probably due to protein modi®cations such as protein phosphorylation or cleavage by proteases (Inbal et al, 1997). These results suggest that DAP kinase may be a key signaling molecule in not only IFN-g but also TNF-a-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 85%
“…It was shown that the reduced expression of DAP kinase mediated by antisense mRNA protected HeLa cells from apoptosis induced by IFN-g, and overexpression of DAP kinase induced apoptosis . DAP kinase has been reported to function as a possible tumor suppressor gene (Kissil et al, 1997;Inbal et al, 1997). Recently, ZIP kinase has been identi®ed by the yeast two-hybrid screening in which the leucine zipper domain of ATF4, a member of Activating Transcription Factor/ cAMP responsive element binding protein (ATF/CREB) family of transcriptional factor was used as a bait .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DAPK loss of expression is associated with a more malignant tumor phenotype and increased metastatic capacity. DAPK is absent in highly metastatic variants of mouse lung cancer cell lines, and is present in the low metastatic variants of those same cell lines (Inbal et al, 1997). In lung and head and neck cancers, DAPK promoter methylation was associated with aggressive disease and poor survival (Sanchez-Cespedes A new paradigm in cell signaling and cancer therapy D Goldschneider and P Mehlen et al, 2000;Tang et al, 2000;Kim et al, 2001;Kong et al, 2005).…”
Section: Drs Are Altered During Tumor Progressionmentioning
confidence: 99%
“…In all, 300 ml of EF5 solution (3 mg/ml) was injected intraperitoneally into mice bearing subcutaneous tumors (Inbal et al, 1997). After 1 h, tumors were surgically removed and frozen in OCT compound.…”
Section: Detection and Microdissection Of Hypoxic Areas In Tumorsmentioning
confidence: 99%
“…There is accumulating evidence that developing resistance to common apoptotic stimuli is one of the factors that confer high metastatic capability to tumor cells (Glinsky and Glinsky, 1996;McConkey et al, 1996;Bufalo et al, 1997;Glinsky, 1997;Inbal et al, 1997;Shtivelman, 1997;Takaoka et al, 1997;Fernandez et al, 2000;Lowe and Lin, 2000;Wong et al, 2001). The apoptosis-resistant phenotype may be advantageous for tumor cells to survive in the metastatic process.…”
Section: Introductionmentioning
confidence: 99%